Fostering secondary school students’ attitudes toward sustainable development and their individual entrepreneurship orientations through a STEM + activity - Handan Ürek; Nilay Korkmaz; Gamze Dolu (Discover Education)
Abstract Today, problems such as climate change, drought, food crises, and pandemics have once again brought the effective use of natural resources back on the agenda. With STEM + based activities, an interdisciplinary learning approach, students are expected to design a product that will solve a problem from daily life and add value to it. Based on these thoughts, this study aims to present a STEM + entrepreneurship activity for secondary school students to design cologne using lavender oil, a natural product. Also, the study aims to determine the impacts of the activity on students’ attitudes toward sustainable development and individual entrepreneurship orientations. In this direction, a single-group pre–test–post–test study was conducted with the attendance of 20 tenth-grade secondary school students. Data was collected with the Individual Entrepreneurship Orientation Scale and Attitudes toward Sustainable Development Scale. The activity was developed according to the engineering design process steps, and a worksheet was used in the implementation, which lasted for four course hours. According to the results, a significant differentiation was determined both in the attitudes toward sustainable development and individual entrepreneurship orientations of the students in favour of post-tests. It is recommended to broaden the context of the activity in future studies.